Liouville type theorems for Hartree and Hartree–Fock equations. (June 2019) - Yang, Jianfu; Yu, Xiaohui
Abstract: In this paper, we establish Liouville type theorems for nonlinear elliptic systems related to Hartree and Hartree–Fock equations in quantum mechanics. The main ingredient we use is the moving plane method.